BOOKLET DEVELOPMENT OF PROTIST MATERIAL FOR CLASS X SMA/MA BASED ON MACROALGAE IDENTIFICATION ON KAUR LAGOON BEACH - Yennita Yennita; Nove Rafika Sintya; Abas Abas; Kasrina Kasrina; Dewi Jumiarni; Abdul Rahman Sinkam (Jurnal IPA Terpadu, 2024)
The Kaur Regency Lagoon Beach is home to a diverse range of macroalgae, presenting an opportunity for various applications. Among these, the development of educational materials, such as booklets for macroalgae identification, stands out. This research aims to catalog the types of macroalgae at Laguna Beach, Kaur Regency, evaluate the suitability of a macroalgae identification-based booklet as educational material for tenth-grade Protista content, and assess the booklet's readability among students. Employing a Research and Development (R&D) approach, macroalgae samples were collected using the cruising method along the shoreline of Laguna Beach. The booklet's effectiveness was validated by media and material experts, as well as two practitioner experts, while its readability was tested with 20 tenth-grade students from SMAN 5 Kaur. The study identified 16 macroalgae species at Laguna Beach, classified into 3 divisions, 9 orders, and 11 families. Specifically, it found 9 Chlorophyta division species (green algae), 2 Rhodophyta division species (red algae), and 5 Phaeophyta division species (brown algae). The booklet validation yielded an average approval rating of 96.34%, categorizing it as 'very good.' The student readability assessment also rated the booklet highly, with a 93.1% approval rate, further supporting its 'very good' classification.